Bioactive Peptides and Proteins from Wasp Venoms - Lei Luo (Biomolecules, 2022)
Wasps, members of the order Hymenoptera, use their venom for predation and defense. Accordingly, their venoms contain various constituents acting on the circulatory, immune and nervous systems. Wasp venom possesses many allergens, enzymes, bioactive peptides, amino acids, biogenic amines, and volatile matters. In particular, some peptides show potent antimicrobial, anti-inflammatory, antitumor, and anticoagulant activity. Additionally, proteinous components from wasp venoms can cause tissue damage or allergic reactions in organisms. These bioactive peptides and proteins involved in wasp predation and defense may be potential sources of lead pharmaceutically active molecules. In this review, we focus on the advances in bioactive peptides and protein from the venom of wasps and their biological effects, as well as the allergic reactions and immunotherapy induced by the wasp venom.